Cognitive impairment and physical frailty in older adults in secondary health care - Bruno Henrique de Mello; Maria Helena Lenardt; Dayana Cristina Moraes; Larissa Sayuri Setoguchi; Marcia Daniele Seima; Susanne Elero Betiolli (SciELO, 2021)
ABSTRACT Objective: To analyze the association between cognitive impairment and physical frailty in older adults in secondary health care. Method: This is a cross-sectional study carried out with people aged ≥ 60 years, assisted at a geriatric and gerontology outpatient clinic. For cognitive screening, the Mini Mental State Examination, the semantic verbal fluency test, and frailty assessment using the physical frailty phenotype were used. The likelihood ratio test was applied to the predictive model. Results: 407 older adults participated in the study. Cognitive impairment was observed in 58.5% (n=238) of the sample, being higher in frail (n=66; 75%). A change in the semantic verbal fluency test was identified in 22% (n=90), with a higher prevalence in pre-frail patients (55.5%; n=226). It was identified 2.5 times more chance of a frail older person, when compared to a non-frail one, to have cognitive impairment (95% CI, +0.947 - 0.322). The chance for alteration in the semantic verbal fluency test was 5.4 times higher in frail compared to non-frail ones (95% CI, 1.68 - 0.38). Conclusion: A relationship was observed between cognitive impairment and physical frailty. Screening for frailty in geriatric nursing practice and the implementation of specific care is recommended.